Simultaneous genotyping for human platelet antigen systems and HLA-A and HLA-B loci by targeted next-generation sequencing - Wang, Jielin; You, Xuan; He, Yanmin; Hong, Xiaozhen; He, Ji; Tao, Sudan; Zhu, Faming (Frontiers in Immunology, 2022)
In order to treat the alloimmunization platelet transfusion refractoriness (PTR), human leukocyte antigen (HLA)-type and/or human platelet antigen (HPA)-type matched platelets between donors and patients are usually used. Therefore, genotyping of HLA-A and HLA-B loci, as well as HPA systems, for donors and patients, is of great significance. However, there is a rare report of genotyping for HLA-A and HLA-B loci as well as HPA systems at the same time. In this study, a high-throughput method for simultaneous genotyping of HLA-A and HLA-B loci, as well as HPA genotyping, was developed. A RNA capture probe panel was designed covering all exon sequences of the GP1BA, GP1BB, ITGA2, CD109, ITGB3, and ITGA2B genes and HLA-A and HLA-B loci. The HLA-A, HLA-B, and 34 HPA systems were genotyped using a targeted next-generation sequencing (NGS) method. The genotypes of the HLA-A and HLA-B loci, as well as the HPA, were assigned based on the nucleotides in the polymorphism sites. Using the NGS method, 204 unrelated blood specimens were successfully genotyped for all 34 HPA systems as well as HLA-A and HLA-B loci. The accuracy of the NGS method was 100%. Only HPA-2, HPA-3, HPA-5, HPA-6w, HPA-15, and HPA-21w showed polymorphism with frequencies of 0.9412, 0.6863, 0.9853, 0.9779, 0.4314, and 0.9951 for a allele, respectively. Thirty-two single nucleotide variants (SNVs) were detected. Of them, 12 SNVs can lead to amino acid change. HLA-A*11:01 and HLA-B*46:01 are the most common alleles for HLA-A and HLA-B loci. A targeted next-generation sequencing method for simultaneously genotyping HPA systems and HLA-A and HLA-B loci was first established, which could be used to create a database of HLA-typed and/or HPA-typed unrelated donors.